2016
DOI: 10.1037/sgd0000163
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination and sexual minority mental health: Mediation and moderation effects of coping.

Abstract: Stigma and discrimination related to sexual minority status are unique stressors associated with mental and physical health concerns among sexual minority individuals. Although some theoretical models propose that the strategies sexual minorities apply to cope with these particular stressors can mediate and/or moderate their impact on mental health outcomes, only a few studies have examined this proposition empirically, typically using measures of broad coping strategies that are not discriminationspecific. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 73 publications
(122 reference statements)
2
20
0
10
Order By: Relevance
“…We specifically examined indirect effects because we assessed coping in response to discrimination and thus were exploring what types of reactions to discrimination may help explain its links with anxiety and depression. This is in line with others’ conceptualizations of coping in other marginalized groups as mediators of the association between marginalization and mental health (e.g., racial minorities: Alvarez & Juang, ; sexual minorities: Ngamake et al, ). In the second approach, we examined whether the various coping responses moderated the association between discrimination and mental health to assess whether the coping strategies may buffer or exacerbate the effects of discrimination.…”
Section: Current Studysupporting
confidence: 89%
See 1 more Smart Citation
“…We specifically examined indirect effects because we assessed coping in response to discrimination and thus were exploring what types of reactions to discrimination may help explain its links with anxiety and depression. This is in line with others’ conceptualizations of coping in other marginalized groups as mediators of the association between marginalization and mental health (e.g., racial minorities: Alvarez & Juang, ; sexual minorities: Ngamake et al, ). In the second approach, we examined whether the various coping responses moderated the association between discrimination and mental health to assess whether the coping strategies may buffer or exacerbate the effects of discrimination.…”
Section: Current Studysupporting
confidence: 89%
“…Although much of the prior research has focused on coping broadly with gender minority stress, as discussed by Ngamake, Walch, and Raveepatarakul (), there are advantages to using measures of coping that are specific to a given stressor (in this case, discrimination). Widely used, broad scales may only capture the ways people cope with stress generally and may not provide the most accurate information for how individuals cope in response to gender minority stressors.…”
Section: Coping With Discriminationmentioning
confidence: 99%
“…Positive psychological and psycho-cognitive processes, such as problem solving and active coping, may mediate the effects of stressors, both general and minority specific, on health (Hatzenbuehler, 2009). Ngamake, Walch, and Raveepatarakul (2016) tested various coping strategies among sexual minority participants as the main mechanism of the relationship between perceived discrimination and psychological distress. Although results only indicated that participants who employed disengagement coping strategies (i.e., substance use) to deal with discriminatory experiences were more likely to report depression, anxiety, and stress symptoms, adaptive coping strategies were also examined, including education, advocacy, and resistance.…”
Section: Health Equity Promotion Modelmentioning
confidence: 99%
“…Numerous studies have demonstrated that discrimination and victimization are associated with depression (Feinstein, Goldfried, & Davila, 2012; Mays & Cochran, 2001; Mustanski et al, 2016; Ngamake, Walch, & Raveepatarakul, 2016; Swann, Minshew, Newcomb, & Mustanski, 2016) and substance use among sexual minority individuals (Bontempo & D’Augelli, 2002; Darwich, Hymel, & Waterhouse, 2012; Espelage, Aragon, Birkett, & Koenig, 2008; Goldbach et al, 2014; Phillips et al, 2017; Wong, Weiss, Ayala, & Kipke, 2010). Research has also demonstrated that the internalization of negative attitudes toward sexual minorities is associated with depression (see Newcomb & Mustanski, 2010), but findings have been mixed for substance use (see Brubaker, Garrett, & Dew, 2009).…”
mentioning
confidence: 99%